Review: Isolasi, Peningkatan Kadar, dan Analisis Calophyllolide dalam Minyak Calophyllum inophyllum Linn. serta Potensinya untuk Terapi Luka Bakar - Herawati, Zainab; Rakhmawati, Rita (Universitas Islam Indonesia, 2025)
Background: Calophyllolide is a dipyranocoumarin compound found in Calophyllum inophyllum L., known for its antimicrobial and anti-inflammatory properties, which are beneficial for burn wound healing. However, variability in its content and lack of standardized methods remain challenges.Objective: This review aims to present a literature study on calophyllolide, including its sources, isolation techniques, bioactive content optimization, analytical methods, and pharmacological potential in burn wound healing.Method: Data were retrieved from Scopus and PubMed using predefined keywords. Articles published in English between 2001 and 2021 and classified as original research were selected. Relevant studies were assessed for quality using the SYRCLE tool (animal studies) and the Young & Solomon checklist (non-clinical research).Results: Seeds harvested in September had the highest calophyllolide content (0.23%). Enhancement through tissue culture using 2 mg/L IBA yielded up to 45.23 mg/100 g callus. Among analytical techniques, a validated GC-MS method showed high precision and recovery. Pharmacological studies confirmed its activity against Staphylococcus aureus and its ability to modulate inflammatory responses.Conclusion: Calophyllolide shows strong potential as a natural agent for burn wound therapy. Standardized extraction, quantification, and production approaches are essential for further development.